A Study to Investigate the Status and Importance of Mental Health and Wellbeing within the Primary School Setting by Exploring Teachers’ Perspectives on the SPHE Curriculum, with Emphasis on a Whole-School Approach. - Collins, Zowie – Cloe (Marino Institute of Education, 2020)
The aim of this research project is to investigate the status and importance of mental health and wellbeing within the primary school setting by exploring teachers’ perspectives on the SPHE curriculum, with emphasis on a whole-school approach. Promoting positive mental health is such an important and worthwhile area, which in the past has been sadly neglected. A quantitative approach was selected for this study, including qualitative questions within the questionnaire. An online questionnaire was selected, which included 50 participants working in a primary school context. The questionnaire sought to uncover the perceptions of primary school teachers in Ireland, regarding the SPHE curriculum and the challenges that accompany it. The main objectives of this study were to, (a) establish the perspectives of primary school teachers on the SPHE curriculum, (b) explore their experience teaching a child with a mental health difficulty, (c) investigate the main issues concerning the SPHE curriculum and (d) determine the importance placed on mental health and wellbeing within the primary school context. Through this a collection of data was uncovered, which was then analysed using descriptive and inferential statistics. The findings assert that the participants hold an overall negative attitude towards the SPHE curriculum. A total of 90% of respondents finding the curriculum outdated and very limiting in supporting children’s mental health needs. These findings give rise to recommendations relating to the curriculum, and that a revised and updated curriculum is necessary in order to tackle the increasing number of mental health difficulties in children in Ireland. Based on the overwhelming concerns it is recommended that schools should consider a whole-school approach in order to implement positive mental health and wellbeing programmes in the classrooms, as well as some much-needed improvement and guidance during initial teacher training education.
Keywords: Research Subject Categories